Review of the Method of Valuation of the SDR. - International Monetary Fund. Finance Dept.. (Washington, D.C. : International Monetary Fund, 2022)
This paper provides the basis for the quinquennial review by the Executive Board of the method of valuation of the Special Drawing Right (SDR). The review covers the composition and weighting of the SDR currency basket, and the financial instruments used to determine the SDR interest rate. In the five-year period for this review (2017-21), developments in key variables relevant for the SDR valuation suggest that there have been no major changes in the roles of currencies in the world economy. The countries and the currency union (euro area) whose currencies are currently included in the SDR basket remain the five largest exporters and their currencies continue to account for the majority of international financial transactions. Moreover, staff analysis finds that the COVID-19 pandemic and recent fintech developments have no systematic or material impact on the SDR valuation. The paper proposes to maintain the current composition of the SDR currency and interest rate baskets, as well as the method for determining the currency weights and currency amounts in the basket. In line with the Board-approved methodology, the paper proposes updated weights for the currencies in the SDR basket. These maintain the same ranking of the initial weights set in the 2015 review, with slightly higher weights for the U.S. dollar and the Chinese renminbi and, accordingly, somewhat lower weights for the British pound, the euro, and the Japanese yen. The paper also proposes to make explicit the treatment of data gaps in the SDR valuation framework. Findings from a survey of SDR department participants and prescribed holders are used to follow up on operational issues raised in earlier valuation reviews. The new SDR valuation and interest rate baskets are proposed to come into effect on August 1, 2022 for a period of five years.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet
Keywords: International Reserves; Monetary Policy; Political Economy; Reserve Currencies; Special Drawing Rights